2020
DOI: 10.1101/2020.11.23.393884
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relationship between serum bilirubin levels, urinary biopyrrin levels, and retinopathy in patients with diabetes

Abstract: Aims/IntroductionPrevious reports have indicated that serum bilirubin levels may be associated with diabetic retinopathy. However, the detailed mechanism is not fully understood. In this study, we evaluated the relationship between the severity of diabetic retinopathy and various factors including bilirubin levels and factors influencing bilirubin metabolism.MethodsThe study participants consisted of 94 consecutive patients with diabetes mellitus admitted to Kyushu University Hospital from April 2011 to July 2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Wan WC et al [22]. found that total bilirubin also has antioxidant properties, so its levels decrease with the advanced diabetic retinopathy stages [23][24][25]. The bilirubin results from the catabolism of Heme in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wan WC et al [22]. found that total bilirubin also has antioxidant properties, so its levels decrease with the advanced diabetic retinopathy stages [23][24][25]. The bilirubin results from the catabolism of Heme in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Its decrease can worsen oxidative stress, leading to the worsening of diabetic retinopathy. Many studies correlated the decrease in total bilirubin with the increased severity of diabetic retinopathy [8]. Many studies showed that there is a strong relation between diabetic retinopathy and serum melatonin levels [9].…”
Section: Introductionmentioning
confidence: 99%